The bookworm - Lavanya, R. N.; Suleman, Shilo Shiv
When bullies pick on ten-year-old Sesha who loves to read and never speaks to anyone, his classmates learn to appreciate his special talents.
Keywords: Children's stories, Indic (English); Stuttering -- Juvenile fiction; Bullying -- Juvenile fiction; Drawing -- Juvenile fiction; Schools -- Juvenile fiction